Cloze Test and Multiple Choice Test for Reading Comprehension. - Erlangga Akbar Medyazarefsi; Evi Rosmiyati; Noviati Noviati (IKIP PGRI Pontianak, 2022)
The objectives of this study are to analyze about the different and similar of multiple choice and cloze test in reading comprehension, and about the perception toward the multiple choice and cloze test among students that influence reading comprehension. This study used descriptive qualitative method. In collecting the data, this study used, Observation, Interview, Questionnaire, and Documentaton. The data were taken by test cloze and multiple choice. This study was conducted to there were 21 informants which were 7 boys and 13 girls of Students and a Teacher of SMA 15 Muara Enim. As a result of this study showed that test was able to make the students tested motivated to learn a lot about English. But there were some who do not understand. In essence, the cloze test and multiple choice test were very suitable to be used as learning test references at SMA 15 Muara Enim.